SUSTAINABILITY STILL A RELEVANT PLATFORM TO INTERNATIONALISE USM RESEARCH GLOBALLY, SAYS DIRECTOR OF EDUCATION MALAYSIA, UK AND IRELAND - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
LONDON, February 2016 – Universiti Sains Malaysia (USM) is recognised internationally as a model of a sustainabilityled university and can expand upon this platform for internationalisation especially in the face of current challenges in funding, said the Director of Education Malaysia United Kingdom and Ireland (EM), Assoc. Prof. Dr. Zainal Abidin Sanusi who stopped by the USM booth at Middlesex University’s education fair held in conjunction with the Erasmus+ International Credit Mobility Staff week 2016.